(untitled) (MAUSAM, 1993)
The spatial distribution of daily rainfall persistence is examined adopting Besson’s persistence coefficient and using daily rainfall data for 15 consecutive years (1971-1985). The daily rainfall persistence coefficients have been studied separately for all the twelve months individually and for the whole year. Where January and February indicate the lowest rainfall persistence coefficients the period from October to December indicates the highest coefficients over Sri Lanka. Besides the monsoonal atmospheric conditions, the topography has a strong influence on the rainfall persistence distribution over space and time. The daily rainfall persistence coefficients record higher values in the wet zone then in the dry zone of Sri Lanka. Regression analysis shows a better linear relationship between mean length of wet spell and the daily rainfall persistence coefficients and the resultant final equation is y.4’ =0.1093+0.1600+X M having the correlation coefficient of 0.721 which is significant at the 0.01% level.